Pengaruh Likuiditas, Reputasi Auditor, Opini Audit dan Komite Audit Terhadap Audit Report Lag - Desak Made Shinta Larasati; Partiwi Dwi Astuti (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2026)
This research is titled "The Influence of Liquidity, Auditor Reputation, Audit Opinion, and Audit Committee on Audit Report Lag." This study aims to examine the effect of liquidity, auditor reputation, audit opinion, and audit committee on audit report lag. The population in this study consists of non-cyclical consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2020. Sampling was determined using the purposive sampling method, resulting in 90 companies used as samples in this study. The type of data used is quantitative data, with secondary data as the data source. The data collection method was carried out using documentation techniques by reviewing the companies' financial statements, yielding 180 data points (90 sample companies $×$ 2 years of observation). Due to the presence of data outliers, 127 data points remained after the outliers were removed. The data analysis technique in this study utilizes multiple linear regression analysis. The results show that liquidity and audit opinion have an insignificant negative effect on audit report lag, auditor reputation has a significant positive effect on audit report lag, and the audit committee has a significant negative effect on audit report lag.